R.G. KUZEYEV’S CONTRIBUTION TO THE STUDY OF THE BASHKIR SHEZHERE - Turgunbayev, E. (Journal of history, 2018)
The contribution of the well-known scientist-ethnologist R.G. Kuzeyev to the study of the bashkir genealogical chronicles – shezhere – the peculiar written monuments of XVI-XIX and sometimes even earlier centuries is considered in the article. Of special interest in the plan of our theme are the studies of R.G. Kuzeyev, in whose works hundreds of bashkir stories, legends, and genealogies have been studied. A special place is given to R.G. Kuzeyev’s scientific research on the identification of shezhere’s handwritten texts, the publication of texts, the creation of shezhere’s corps, the concentration of handwritten texts in the archives, the purposeful work to find, collect and study the ancient texts of the genealogical chronicles shezhere. The author notes Kuzeyev’s invaluable contribution to the development of a comprehensive approach to ethnogenetic research.